Riemann integral and its relation with Lebesgue integral - Bhattrai, Mani Raj (BIBECHANA, 2010)
This review explains the limitations of the Riemann integral and focuses on the more general concept. It has been suggested that a better route is to abandon the Riemann integral for Lebesgue integral and explained the importance of Lebesgue integral in real analysis and other fields of mathematical science. Keywords: Riemann integral; Lebesgue integral; Fourier series DOI: 10.3126/bibechana.v7i0.4051 BIBECHANA 7 (2011) 83-86